Status of the BNL muon (g-2) experiment - Prigl, Ralf; Grossmann, Alex; Jungmann, Klaus; Neumayer, Paul; Putlitz, Gisbert zu (IEEE transactions on instrumentation and measurement, 1999)
The muon (g-2) experiment at Brookhaven completed a first run in June and July 1997. The main components of the experiment, which include the superconducting inflector, the superferric storage ring, the electrostatic quadrupoles and the lead-scintillating fiber electron calorimeters, have been commissioned satisfactorily. Our first measurement of the ratio R of the spin precession frequency of the positive muon relative to that of a free proton, R=(3.707219±0.000048)×10-3, is in good agreement with the previous CERN measurements for μ+ and μ- , and has approximately the same uncertainty as each of these measurements. In spring 1998 a muon kicker was installed and successfully tested in the storage ring magnet and a significant improvement in the knowledge of the muon g-factor is expected from upcoming runs in August 1998 and January 1999